2012
DOI: 10.1089/ars.2011.4336
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Physiology and Pathology by Protein S-Glutathionylation: Lessons Learned from the Cardiovascular System

Abstract: Significance: Reactive oxygen and nitrogen species contributing to homeostatic regulation and the pathogenesis of various cardiovascular diseases, including atherosclerosis, hypertension, endothelial dysfunction, and cardiac hypertrophy, is well established. The ability of oxidant species to mediate such effects is in part dependent on their ability to induce specific modifications on particular amino acids, which alter protein function leading to changes in cell signaling and function. The thiol containing am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 184 publications
(186 reference statements)
3
71
0
1
Order By: Relevance
“…Thus, antibodies directed against specific glutathionylated peptides of key regulatory proteins would facilitate in situ analysis of specific signaling intermediates, and specific glutathionylated peptides could be used as internal standards for quantitative mass spectrometric analyses of changes in protein-SSG under different physiological or pathophysiological conditions. For other perspectives and more critical discussion of current methods, see this Forum (21,30), as well as previous reviews (1,7,10,22,25).…”
Section: Mieyal and Chock Limited Methodology For Characterization Ofmentioning
confidence: 99%
“…Thus, antibodies directed against specific glutathionylated peptides of key regulatory proteins would facilitate in situ analysis of specific signaling intermediates, and specific glutathionylated peptides could be used as internal standards for quantitative mass spectrometric analyses of changes in protein-SSG under different physiological or pathophysiological conditions. For other perspectives and more critical discussion of current methods, see this Forum (21,30), as well as previous reviews (1,7,10,22,25).…”
Section: Mieyal and Chock Limited Methodology For Characterization Ofmentioning
confidence: 99%
“…Importantly, glutathionylation can be reversed in a reducing environment, in an enzyme-dependent or independent manner (7,13,15,36,58). Notably, a previous report (9) showed that RBC protein glutathionylation (mainly Hb) in human blood decreased immediately after the oxidative challenge and increased again in parallel with the modification of the GSH-GSSG ratio.…”
Section: Discussionmentioning
confidence: 97%
“…The indication that Hb deglutathionylation was a likely mechanism explaining the CO-mediated GSH increase in RBCs led us to investigate the involvement of enzymes known to favor this reaction such as GR, glutaredoxin (25), Trx/TrxR, or sulfiredoxin (Srx) (13,25,32,36) (Fig. 8A).…”
Section: Co Increases the Activity Of Gr In Rbcsmentioning
confidence: 99%
“…Recent studies suggest that the NO-mediated pathway and the ROS-mediated pathway may have extensive crosstalk (37,93,132); the reaction between NO and superoxide gives rise to peroxynitrite, which can be a potent mediator of S-glutathionylation in the presence of GSH; NO may form protein-SNO, which can serve as a precursor to protein-SSG. And in the case of RyR channels, S-nitrosylation and S-glutathionylation may compete for the same cysteine residues (4).…”
Section: Ion Channel S-nitrosylation and Its Relationship With S-glutmentioning
confidence: 99%
“…Oxidative stress, or reactive oxygen species (ROS), facilitates S-glutathionylation. Protein S-glutathionylation has been extensively discussed in many excellent reviews with a variety of different emphases (31,44,45,75,76,88,93,100,107). Over the past few years, S-glutathionylation has been increasingly observed in many ion channels, such as voltage-gated calcium channels, ryanodine receptor (RyR), and ATP-sensitive potassium channels (K ATP channels), all of which contribute to critical cellular functions (4,123,137,138).…”
Section: Introductionmentioning
confidence: 99%